Innovativeness of the Polish economy in relation to the Visegrad Group countries - Edyta Dworak; Maria Magdalena Grzelak (Economic and Environmental Studies (E&ES), 2018)
In March 2017, the Warsaw Declaration was signed, establishing provisions for the strategic alliance of the Visegrad Group countries, in the framework of which innovativeness is to become a new element of the cooperation between its members. The Warsaw Declaration provides for the initiation of cooperation between governmental agencies, research institutions, universities and local governments in the V4 countries. Within the framework of the envisaged cooperation, Poland has the ambition to become the leader of innovativeness in the group. In the context of the Warsaw Declaration objectives concerning close cooperation in the field of enhancing the innovation potential of the Visegrad Group's economies, the assessment of the level of innovativeness of the Polish economy in relation to the other countries of the group is important. The aim of the paper is, therefore, to make a comparison of this potential on the basis of the summary innovation index, published in the annual report of the European Commission entitled European Innovation Scoreboard, as well as on the basis of the components of this index. In the article, there was conducted a literature review on the innovativeness of the Polish economy, a descriptive analysis, an analysis of statistical data in time and a comparative analysis. The authors proposed also the research thesis that the Polish economy shows a weaker innovation potential than those recorded for the other countries of the group. Results of the research confirm the thesis to some extent. Poland holds a dominant position only in a few areas describing the innovation potential and for most of the studied indices the Polish economy is located 'in the tail' of the group
Keywords: C31; C34; C38; 330; innovativeness; Visegrad Group (V4); summary innovation index (SII); European Innovation Scoreboard (EIS)